Synthesis, Identification and Evaluation Biological Activity for Some New Triazole, Triazoline and Tetrazoline Derivatives From 2-Mercapto-3-phenyl-4(3H)Quinazolinone - Al-Sultani, Khitam T. A.; Al-Majidi, Suaad M. H.; Al-Jeilawi , Oday H. R. (Iraqi Journal of Science, 2023)
This research, involved synthesis of some new 1,2,3-triazoline and 1,2,3,4-tetrazole derivatives from antharanilic acid as starting material .The first step includes formation of 2-Mercapto-3-phenyl-4(3H)Quinazolinone (0) through reacted of anthranilic acid with phenylisothiocyanate in ethanol, then compound (0) reaction with chloro acetyl chloride in dimethyl foramamide (DMF) to prepare intermediate S-(α-chloroaceto-2-yl)-3-phenylquinazolin-4(3H)-one (1); compound (1) reacted with sodium azide to yield S-(α-azidoaceto-2-yl)-3-phenylquinazolin-4(3H)-one (2), while Schiff bases (3-10) were prepared from condensation of substituted primary aromatic amines with different aromatic aldehydes in absolute ethanol as a solvent. Compound (2) reacted with Schiff bases to give 1,2,3,4-tetrazoline derivatives (11-18) which was entered in 1,3-dipolar cyclo addition reactions with some of α,β-unsaturated carbonyl compounds to give 1,2,3-triazoline (19-24) and triazole (25-27) derivatives respectively. The structure of newly synthesized compounds were identified by spectral methods their [Fourier transform infrared (FTIR) and some of them 1H-NMR, 13C-NMR] and measurements some of its physical properties and some specific reactions. Furthermore were studied the effects of the preparing compounds on some strains of bacteria.